Effect of (1,4) phenylenediamine on the corrosion of lead in 1M hydrochloric acid solution (Baghdad Science Journal, 2007)
The accelerating effect of 1,4- phenylenediamine (PDA) additions in 1M hydrochloric acid solution at temperature rang (20-60) C° has been studied by weight losses measurement during ranging time (1-260) h and by following the pb2+ concentration in solution after several times by using Atomic absorption spectroscopy (AAS) . The volume of hydrogen gas involving was followed also in presence and absence of (PDA) in the corrosive solution .Accelerating enhanced by adding (NaCl , NaBr , NaI ) was also investigated.